Risk factors for long-term outcome in photoselective vaporization of the prostate - Popeneciu, Valentin; Hatiboglu, Gencay; Kuru, Timur Hasan; Milakovic, Sandra; Freier, Gerald Jörg; Hadaschik, Boris; Hohenfellner, Markus; Pahernik, Sascha (Scandinavian journal of urology, 2016)
OBJECTIVE: The aim of this retrospective cohort study was to investigate long-term risk factors for reintervention after photoselective vaporization of the prostate (PVP). - MATERIAL AND METHODS: In total, 566 consecutive patients with benign prostatic hyperplasia (BPH) underwent PVP between February 2005 and April 2011. Mean follow-up was 36.42 ± 21.4 months. Perioperative parameters were evaluated, including surgery time, delivered energy, catheterization and duration of hospitalization, intraoperative and postoperative complications, as well as reintervention rates in manifest reobstruction. Follow-up comprised the International Prostate Symptom Score and quality of life questionnaire (IPPS-QoL), maximal flow rate (Qmax) and postvoiding residual volume (PVR). - RESULTS: Mean operation time was 69.8 ± 29.3 min. Mean catheterization and hospitalization times were 1.49 ± 1.19 days and 2.67 ± 2.19 days, respectively. There was ongoing oral anticoagulation for 20.1% of the patients (n = 114). The overall retreatment rate was 17.6% (101 out of 566 patients) after a mean time of 9.21 months (range 0-64 months). Of these, 88 patients (15.55%) had a reobstruction and 13 (2.3%) had urethral strictures. In multivariate analysis, age, prostate volume, total applied energy, specific laser energy usage, preoperative symptomatic (IPSS/QoL) and functional obstruction grade (Qmax/PVR) were not identified as risk factors for reintervention. A poor postoperative Qmax (< 15 ml/s) measured immediately after removal of the transurethral catheter was identified as a risk factor for undergoing a reintervention (p = 0.005). - CONCLUSIONS: PVP is an effective method for BPH treatment, allowing for sustained long-term improvement of the voiding function. Poor immediate postoperative urinary flow after removal of the transurethral catheter (Qmax < 15 ml/s) is a significant risk factor for reintervention.
Published online: 29 Apr 2016
Gesehen am 03.11.2020